Effectiveness Work from Home to Completing the Work During Covid-19 for Millennial Workers - Setyani, Komang Dian Trisna (Universitas Pamulang, 2023)
When Pandemic Covid 19 entered Indonesia, the Indonesian government gave rules to always wash their hands, wear masks, to keep distance from each other or reduce physical contact with people in the outside environment. With the regulations issued by the government as a step to reduce the transmission of covid 19, the office and industry also take measures to assign workers to work from home (WFH). WFH is a new thing for workers in Indonesia. This research specializes in Millennial generation because they are known as the generation that is active in the organization or work. This research was conducted with the aim to determine the effectiveness of millennial workers in completing work tasks during the work from home. The research used a qualitative method with in-depth interview techniques. Characteristics of respondents taken were millennial workers in surabaya with an age range of 24-30 years who had been work from home for 3 months. The results of this study indicate that millennial workers are effective in completing work assignments while work form home. WFH also provides an advantage for them to be more flexible in their work without any limitation of time even though they are also capable of performing other activities (such as webinars) while working.